Preparation and high CO2/CH4 selectivity of ZSM-5/Ethyl cellulose mixed matrix membranes. (17th February 2021) - Xu, Shuangping; Zhou, Hailiang; Jia, Hongge; Xu, Jingyu; Liu, Da; Zhang, Mingyu; Qu, Yanqing; Ma, Wenqiang; Jiang, Pengfei; Zhao, Wenwen; Wang, Xintian
Abstract: It is known that natural gas is extracted with a large amount of CO2, which reduces the amount of heat generated during the combustion of natural gas. How to remove some of the CO2 from the natural gas is a problem that needs to be solved. The significant breakthroughs of the membrane technology, specifically the mixed matrix membrane (MMM) has revealed a promising CO2 /CH4 separation performance. In this study, a series of ZSM-5/EC mixed matrix membranes with ethyl cellulose (EC) as matrix and ZSM-5 as inorganic dispersant in tetrahydrofuran were prepared under high speed and ultrasonic vibration-assisted, the ZSM-5/EC membranes were fabricated by using the casting solution. The successful ZSM-5/EC mixed matrix membranes were confirmed by Fourier transfer infrared (FTIR) and Scanning electron microscopy (SEM). The ZSM-5/EC membranes exhibited good membrane forming ability, heat resistance and mechanical properties; The CO2 /CH4 selectivity of the ZSM-5/EC membranes were 10.7, 15.4, 19.7, 25.5 and 11.7, respectively, increased up to 1.3, 1.9, 2.4, 3.1 and 1.4 times as compared to pure EC (8.20) with a feed composition of 50:50 for CO2 /CH4 .